Odpowiedź :
/-kreska ułamkowa
obliczamy q
q=-1/1/√3-√2
q=-1×(√3-√2/1)
g=-√3+√2
a5=a1×qdo potęgi 4
a5=1/√3-√2×(-√3+√2)do potęgi4
a5=1/√3-√2×12
a5=12/√3-√2
usuwamy niewymierność z mianownika
a5=12√3+12√2/3-2
a5=12√3+12√2/1
a5=12√3+12√2
obliczamy q
q=-1/1/√3-√2
q=-1×(√3-√2/1)
g=-√3+√2
a5=a1×qdo potęgi 4
a5=1/√3-√2×(-√3+√2)do potęgi4
a5=1/√3-√2×12
a5=12/√3-√2
usuwamy niewymierność z mianownika
a5=12√3+12√2/3-2
a5=12√3+12√2/1
a5=12√3+12√2
q=-1/1/√3-√2
q=-1×(√3-√2/1)
g=-√3+√2
a5=a1× do potęgi 4
a5=1/√3-√2×(-√3+√2)do potęgi4
a5=1/√3-√2×12
a5=12/√3-√2
a5=12√3+12√2/3-2
a5=12√3+12√2/1
a5=12√3+12√2
q=-1×(√3-√2/1)
g=-√3+√2
a5=a1× do potęgi 4
a5=1/√3-√2×(-√3+√2)do potęgi4
a5=1/√3-√2×12
a5=12/√3-√2
a5=12√3+12√2/3-2
a5=12√3+12√2/1
a5=12√3+12√2